Effectiveness of diabetes self-management education on distress and HbA1C among Indian Type 2 diabetes mellitus patients: A randomized controlled trial - M Anjali; Meenakshi Khapre; Ravi Kant; Santosh Kumar; Pragya Pandey (Indian Journal of Community Medicine, 2023)
Introduction: The interrelationship of diabetes with mental illness has increased in recent years. Diabetes-related distress is the emotional burden, stress, and worries associated with diabetes, which does not reach the threshold for depressive disorder. A diabetes self-management education (DSME) is a structured educational approach to improve glycemic control and diabetes-related distress. This study aimed to assess the effectiveness of DSME in comparison with usual diabetes care in improving glycemic control and diabetes-related distress. Material and Methods: This is a single-center, parallel randomized controlled trial. A total of 106 participants were recruited for both intervention and control groups with 53 participants each. The control group received only routine outpatient department (OPD) care. The intervention group received DSME in addition to routine OPD care. Diabetes-related distress and HbA1C were assessed after 3 months. The data were analyzed using IBM Statistical Package for the Social Sciences (SPSS) version 25. Per-protocol analysis was done. Results: Of 127 patients screened, 106 met the eligibility criteria and were randomized. At 3-month follow-up, the reduction in mean HbA1C, fasting blood sugar (FBS), postprandial blood sugar (PPBS), and diabetes distress were significant in the intervention group compared with the control group (p 0.001). The mean HbA1C reduction in the intervention group was significant (mean difference: -1.3, SD: 0.4). The mean DDS had decreased significantly in the intervention group from 2 to 1.2 (mean difference: -0.8, SD: 0.1). Conclusion: The DSME was effective in improving the glycemic control, diabetes-related distress, and self-care among type 2 diabetes (T2DM) mellitus patients.